Cinema verite [videorecording (DVD)] - Berman, Shari Springer; Pulcini, Robert; Lane, Diane; Robbins, Tim, 1958-; Gandolfini, James (HBO Home Video, 2012)
The behind-the-scenes story of 'An American Family', the revolutionary 1970s PBS documentary centered around the Loud family that launched a new television genre: reality TV.